Central diabetes insipidus induced by temozolomide: A report of two cases. (June 2021) - Mahiat, Cédric; Capes, Antoine; Duprez, Thierry; Whenham, Nicolas; Duck, Lionel; Labriola, Laura
Introduction: Central diabetes insipidus is a heterogeneous condition characterized by decreased release of antidiuretic hormone by the neurohypophysis resulting in a urine concentration deficit with variable degrees of polyuria. The most common causes include idiopathic diabetes insipidus, tumors or infiltrative diseases, neurosurgery and trauma. Temozolomide is an oral DNA-alkylating agent capable of crossing the blood-brain barrier and used as chemotherapy primarily to treat glioblastoma and other brain cancers. Cases: Two men (aged 38 and 54 years) suddenly developed polyuria and polydispsia approximately four weeks after the initiation of temozolomide for a glioblastoma. Plasma and urine parameters demonstrated the presence of a urinary concentration defect. Management: The clinical and laboratory abnormalities completely resolved with intranasal desmopressin therapy, allowing the continuation of temozolomide. The disorder did not relapse after cessation of temozolomide and desmopressin and relapsed in one patient after rechallenge with temozolomide. Discussion: Our report highlights the importance of a quick recognition of this exceptional complication, in order to initiate promptly treatment with desmopressin and to maintain therapy with temozolomide.